VALUE ASSESSMENT OF FRUIT ORCHARDS BASED ON THE COSTS OF ESTABLISHMENT - Lukač Bulatović, Mirjana; Đurić, Katarina; Marković, Todor (Economics of Agriculture, 2024)
The necessity for value assessment of fruit orchards (an orchard as a whole and/or individual fruit trees grown therein) arises in instances of the damage or destruction of orchards caused by climatic factors, intentional harm, expropriation, the construction of public facilities at the orchard site (such as highways, railways, power lines, etc.), changes in ownership, and expert mediation in various legal disputes. The value assessment of orchards based on the total costs of establishment involves determining all expenditures incurred from the very establishment of the orchard until its full development, id est until reaching such productivity that the value of production exceeds the incurred production costs and the annual annuity payment. The theoretical-methodological procedure for assessing the value of fruit orchards based on the total costs of establishment, or their cultivation value, is illustrated using a peach orchard as an example.